Condition of Food Sanitation and Hygiene in East Bandung, West Java - Epa Paujiah; Maratus Solikha; Yani Suryani (UIN Sunan Gunung Djati Bandung, 2018)
Food security is one of the health problems in Indonesia which is related to the lack of knowledge of how the production process, the hygiene and health of the food. This study aims to describe the sanitary and hygienic conditions of food sold by merchant in Cibiru, Bandung City, West Java. The study was conducted in May-June 2017 by determining five sampling location based on the number of merchant in Cibiru. Data was obtained through questionnaire filling of 40 respondents at each sampling point which was then analyzed to find out the characteristics of social-demographic of the respondents, personal hygiene, and support of environmental sanitation. The results shows that the sanitation and hygiene of food in the aspect of knowledge of personal hygiene showed that the food handler was experienced food processors (88%) and 12% had no experience even though their last education was not linear with their trading profession. In addition, respondents' knowledge of individual hygiene shows that out of the nine aspects observed, 33% are in the high category, 11% are moderate and 56% are in the low category. Aspects of environmental sanitation and other support of food sanitation show that the conditions are in the clean and adequate category. All of these aspects can be used as a basic consideration in further counseling about food hygiene and food processing so that it can avoid unpredictable outbreaks.